The design of a network command language : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Computer Science at Massey University - Jenkins, Phillip Campbell (Massey University, 1980)
Most computer series have their own distinct operating system control language. At present there is no world-wide standard control language, but the recent development of heterogeneous networks, where users may access many different computers, has highlighted the need for one. A project to set up an experimental network, called KIWINET, between Massey and Victoria Universities, initiated research into the design of a standard control language for the network. The result of this research is a high-level, block structured language called the Network Command Language (NCL). The design of this language and its implementation are discussed.
Keywords: Computer networks; Programming languages (Electronic computers); Kiwinet (Information retrieval system)